2014
DOI: 10.1183/09031936.00046114
|View full text |Cite
|
Sign up to set email alerts
|

Function of monocytes and monocyte-derived macrophages in α1-antitrypsin deficiency

Abstract: α 1 -antitrypsin deficiency is the most widely recognised genetic disorder causing chronic obstructive pulmonary disease (COPD). Mutant Z α 1 -antitrypsin expression has previously been linked to intracellular accumulation and polymerisation of this proteinase inhibitor. Subsequently, this has been described to underlie an exaggerated endoplasmic reticulum stress response and enhanced nuclear factor-κB signalling. However, whether monocyte-derived macrophages display the same features remains unknown.Monocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Although polymers formed from the folded state are typically studied because of experimental ease of generation, they might nevertheless still be of physiological and pathological importance, since it has been observed that polymers of Z α 1 PI also occur in circulation [62] and are even found to co-localize with neutrophils in lung alveoli [63], though not within the neutrophils [64]. Understanding whether such polymers use the same mechanism of formation as polymers formed intracellularly during folding is therefore of high significance.…”
Section: Folding and Polymerizationmentioning
confidence: 99%
“…Although polymers formed from the folded state are typically studied because of experimental ease of generation, they might nevertheless still be of physiological and pathological importance, since it has been observed that polymers of Z α 1 PI also occur in circulation [62] and are even found to co-localize with neutrophils in lung alveoli [63], though not within the neutrophils [64]. Understanding whether such polymers use the same mechanism of formation as polymers formed intracellularly during folding is therefore of high significance.…”
Section: Folding and Polymerizationmentioning
confidence: 99%
“…Alpha-1 antitrypsin (AAT), a major serine proteinase inhibitor (Serpin), is synthesized primarily in the liver, but is also produced in extra-hepatic tissues and cells, including neutrophils, monocytes, alveolar macrophages, and intestinal and corneal epithelium [1]. AAT functions primarily to protect lung tissue from the destructive effects of serine proteases, such as neutrophil elastase, proteinase 3 and cathepsin G, which are released by degranulating neutrophils [2]. Although AATs are associated with maintaining protease-antiprotease homeostasis, their principle efficiency is in regulating inflammatory responses rather than inhibiting specific proteases [3].…”
Section: Introductionmentioning
confidence: 99%
“…We also consider existing treatment options and developments that 7 might further improve the outlook for 1-antitrypsin deficient individuals. 8 9 10 [H1] Epidemiology 11 1-antitrypsin deficiency is relatively common but widely and persistently under-12 recognized 2,3 . This section considers the world-wide prevalence of 1-antitrypsin 13 deficiency, evidence that it is under-recognized, and the reasons for under-recognition.…”
mentioning
confidence: 99%
“…Estimates of the mean interval between first symptom (usually dyspnoea) and initial 11 diagnosis range from 5.6 -8.3 years 3,9 . Diagnostic delay intervals remain as long in 12 studies from 2013 as they were in the earliest study in 1995, suggesting little 13 improvement in detection pace over nearly two decades despite the publication of many 14 guidelines 10 which recommend that all COPD patients should be tested for 1-antitrypsin 15 deficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation